2019
DOI: 10.1039/c9ra04278d
|View full text |Cite
|
Sign up to set email alerts
|

Paper-based microfluidic devices based on 3D network polymer hydrogel for the determination of glucose in human whole blood

Abstract: In this study, optical microfluidic paper analytical devices (μPADs) for glucose detection from whole blood samples with a small sample volume (2 μL) have been developed on a single paper.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 38 publications
1
5
0
Order By: Relevance
“…He et al also found that 2 μl of blood is the best blood volume. [77] Using this method, analysis of the sample can be completed in 1 min, and the detection results are consistent with the results obtained using the blood glucometer, proving the feasibility of the analytical device. To prove the validity of this method, a sample with a blood glucose concentration of 3-200 mM was used to form a comparison with a human whole blood sample in the experiment.…”
Section: Microfluidic Applications In Blood Testingsupporting
confidence: 79%
See 2 more Smart Citations
“…He et al also found that 2 μl of blood is the best blood volume. [77] Using this method, analysis of the sample can be completed in 1 min, and the detection results are consistent with the results obtained using the blood glucometer, proving the feasibility of the analytical device. To prove the validity of this method, a sample with a blood glucose concentration of 3-200 mM was used to form a comparison with a human whole blood sample in the experiment.…”
Section: Microfluidic Applications In Blood Testingsupporting
confidence: 79%
“…(D) Sample experiments of whole blood on μPAD based on different papers. [77] (Color figure can be viewed at the Royal Society of Chemistry) plasma from red blood cells agglutination. Recently, Tseng et al [84] developed a 3D μPAD to detect the human whole blood creatinine.…”
Section: Microfluidic Applications In Blood Testingmentioning
confidence: 99%
See 1 more Smart Citation
“…Immobilization of glucose sensing reagents in the gel material is important for ensuring the operational stability of glucose biosensor response . A number of papers have reported the immobilization of glucose-sensing reagents in gel to perform glucose sensing and applied such methods to various sensing mechanisms, including electrochemical, fluorescence, , surface plasmon resonance, , luminescence, , and colorimetry , methods. Colorimetry is one of the simplest forms of detection and thus commonly used in many glucose POC diagnosis methods.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to the devices for glucose detection in skin ISF including fluorescence [122], frequency [77,83], electrical [124] etc. and tear including structure color [74,87,[125][126][127], etc., there are many studies suitable for blood including structure color [115,126], fluorescence [39,40,104], electrical [109], etc. and urine including structure color [128,129], electrical [93] etc.…”
Section: Othersmentioning
confidence: 99%